Analisis optimalisasi dan revitalisasi aset pasar tradisional Pandansari di Kota Balikpapan: Analisis kebutuhan dan ekonomis - Bagaskara, Bagaskara; Harimawan, Rosario Guntur; Maulana, Iqbal Rizky (Journal of Economics Research and Policy Studies, 2024)
Pandansari Market is one of the markets with great potential located in Balikpapan City. However, this market is still not optimal in its management and utilization. This study aims to identify the needs of buyers and traders as a basis for formulating policy recommendations. Economic aspects play an important role as an indicator of optimal utilization. This study uses primary and secondary data. Primary data was obtained through surveys and Focus Group Discussions (FGD). This study uses several analysis methods such as needs analysis, Strength Weakness Opportunity Threat (SWOT) analysis, and Cost Benefit Analysis (CBA) analysis. Based on the results of the study, it is necessary to optimize and revitalize Pandansari Market. Strategies that can be carried out to optimize Pandansari Market are divided into two, namely physical and non-physical strategies. Based on the calculation results, the revitalization alternative that provides the greatest benefit for Pandansari Market is utilization as a food court. This is based on the benefit and cost ratio of 14.64 (taking into account social benefits). In addition to being financially and economically feasible, utilization as a food court can attract a wider consumer demographic. This is important to ensure the sustainability of traditional markets.